2018
DOI: 10.1097/md.0000000000011403
|View full text |Cite
|
Sign up to set email alerts
|

Congenital asymmetric crying facies syndrome

Abstract: Introduction:Congenital asymmetric crying facies (ACF) in newborns is a rare condition usually caused by unilateral agenesis or hypoplasia of the depressor anguli oris muscle on one side of the mouth (symmetric face at rest and asymmetric face while crying), which is often accompanied with other malformations.Case report:We present a case of a female newborn with nonconsanguineous ethnic Han Chinese parents who presented with 37 minutes of breathlessness and asymmetrical face when crying. A thorough physical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…The etiology includes facial nerve compression and faulty facial muscle/nerve development. An asymmetric crying face is often seen in 22q11.2 deletion syndrome patients; however, it has not been reported in CHARGE syndrome patients [25, 26]. This could be because the importance of this symptom has not received enough attention.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology includes facial nerve compression and faulty facial muscle/nerve development. An asymmetric crying face is often seen in 22q11.2 deletion syndrome patients; however, it has not been reported in CHARGE syndrome patients [25, 26]. This could be because the importance of this symptom has not received enough attention.…”
Section: Discussionmentioning
confidence: 99%
“…CHDAOM can present as an isolated finding but also can occur with other congenital malformations in up to 45%-70% of cases [3][4][5]. These malformations are not limited to any particular body system, but most commonly involve the head and neck regions and cardiovascular system [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…When CHDAOM is seen among a collection of other exam findings suggesting congenital disease, it is most notably associated with syndromes such as DiGeorge syndrome, VACTERL (Vertebral anomalies, Anal atresia, Cardiac defects, Tracheo-Esophageal fistula, Renal anomalies, Limb defects) association, and Cayler cardiofacial syndrome among others [4][5][6]. CHDAOM itself is a clinical diagnosis and is a benign condition when occurring in isolation, yet it has been suggested that the diagnosis of CHDAOM may be an indicator of concomitant congenital abnormalities [1,4,6]. Therefore, thorough physical examination and comprehensive newborn screening must be performed to either rule out any of the aforementioned syndromes or to begin prompt treatment and correction of the more serious coexisting abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…When deviation of the mouth is not associated with other asymmetric features of the face and appears only during crying, as in case 1, the diagnosis is a congenital agenesis or hypoplasia of the depressor anguli oris muscle (DAOM). This minor congenital anomaly affects 0.6% of infants, and occurs on the left side in 80% of cases 1. It becomes evident when the baby cries or laughs, with a depression of the corner of the lower lip on the unaffected side 2.…”
Section: Answermentioning
confidence: 99%
“…When compared with agenesis/hypoplasia of the DAOM, facial palsy is characterised by paresis of the whole hemiface with the inability to wrinkle the forehead, close the eyelid, maintain a nasolabial fold and dilate the nostril of the affected side. The asymmetry persists at rest 1. A third rarer condition causing neonatal asymmetric face is cranial microsomia.…”
Section: Answermentioning
confidence: 99%